LTES with PCM and metal foam in convergent and divergent shell and tube configurations assuming external heat loss - Renato Elpidio Plomitallo; Bernardo Buonomo; Oronzio Manca; Sergio Nardini; Giulia Righetti; Simone Mancin (Science Talks)
Thermal energy storage (TES) systems have become highly relevant due to the need to cut carbon emissions, and one of the most promising TES systems is the latent heat one (LTES) based on phase change materials (PCMs). However, the low thermal conductivity and poor heat transfer capabilities of PCMs limit their performance. The LTES, which in this study incorporate phase change materials (PCMs) and metal foams, offer key benefits over traditional sensible heat storage options. The inclusion of metal foams increases the thermal conductivity of PCMs. This research examines a vertical shell-and-tube setup with a non-uniform internal tube cross-section, considering two different configurations: convergent internal tube and divergent one. It is also considered an inclination angle variation of the internal tube. In addition, it is made the assumption of external heat losses on the lateral surface. Heat transfer and phase change processes are analyzed using the Brinkman-Forchheimer-extended Darcy model and the enthalpy-porosity approach. The numerical solutions are performed through Ansys-Fluent. Findings indicate that LTES systems using metal foam and PCM have improved heat transfer, particularly in configurations with converging tube sections. Although higher heat loss during the melting, the convergent configuration has the faster melting time at each inclination angle.